Current prophylactic plasma infusion protocols do not adequately prevent long‐term cumulative organ damage in the Japanese congenital thrombotic thrombocytopenic purpura cohort. (28th May 2021) - Sakai, Kazuya; Fujimura, Yoshihiro; Miyata, Toshiyuki; Isonishi, Ayami; Kokame, Koichi; Matsumoto, Masanori
Summary: Congenital thrombotic thrombocytopenic purpura (cTTP), known as Upshaw–Schulman syndrome, is an ultrarare thrombotic disorder caused by ADAMTS13 gene mutations; however, its long‐term outcomes have not been widely studied. A questionnaire survey was administered to physicians of patients in the Japanese cTTP registry to characterise these outcomes. We analysed 55 patients in remission, with 41 cases receiving prophylactic fresh frozen plasma (FFP; median dosage: 13·2 ml/kg per month) and 14 receiving on‐demand FFP. Patients receiving prophylactic FFP were considered as having a more severe form of the disease and had lower platelet counts and higher serum creatinine levels than those receiving on‐demand FFP (median 138 × 10 9 /l vs. 243 × 10 9 /l, P = 0·003 and 0·71 mg/dl vs 0·58 mg/dl, P = 0·009, respectively). Patients who received prophylactic FFP more commonly developed organ damage, including renal impairment, cerebral infarctions, and cardiac hypofunction, than those who did not. Adverse FFP‐related events were seen in 78% of the prophylactic FFP group, with allergic reactions being most common. Since current protocols for FFP administration to the prophylactic FFP group in Japan may be insufficient for preventing cumulative organ damage, a higher dosage of ADAMTS13 supply using recombinant ADAMTS13 agent is needed in these patients.